2010
DOI: 10.1038/embor.2010.185
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase 7 has a conserved role in Wnt/β‐catenin canonical signalling

Abstract: The receptor protein tyrosine kinase 7 (PTK7) was recently shown to participate in noncanonical Wnt/planar cell polarity signalling during mouse and frog embryonic development. In this study, we report that PTK7 interacts with b-catenin in a yeast two-hybrid assay and mammalian cells. PTK7-deficient cells exhibit weakened b-catenin/T-cell factor transcriptional activity on Wnt3a stimulation. Furthermore, Xenopus PTK7 is required for the formation of Spemann's organizer and for Siamois promoter activation, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
109
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 14 publications
5
109
3
1
Order By: Relevance
“…Indeed, PTK7 is implicated in the canonical and noncanonical Wnt pathways (17,39), which are thought to be the guardians of the balance between HSC selfrenewal and HSC differentiation (32). We showed recently that PTK7 plays a role in the canonical pathway downstream of Wnt3a, suggesting that deficiency in PTK7 may mirror deficiency in Wnt3a (25). This would be consistent with results showing that Wnt3a deficiency leads to a reduction in the numbers of HSPCs in the FL but would not fit with the reduced reconstitution capacity observed in secondary transplantation assays of Wnt3a-deficient cells, which is not observed with Ptk7-deficient cells (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, PTK7 is implicated in the canonical and noncanonical Wnt pathways (17,39), which are thought to be the guardians of the balance between HSC selfrenewal and HSC differentiation (32). We showed recently that PTK7 plays a role in the canonical pathway downstream of Wnt3a, suggesting that deficiency in PTK7 may mirror deficiency in Wnt3a (25). This would be consistent with results showing that Wnt3a deficiency leads to a reduction in the numbers of HSPCs in the FL but would not fit with the reduced reconstitution capacity observed in secondary transplantation assays of Wnt3a-deficient cells, which is not observed with Ptk7-deficient cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Such a function of PTK7 in the Wnt5a-mediated noncanonical pathway would fit with the PCP function of PTK7 and with the altered homing and migrating properties of Ptk7-deficient cells that likely depend on small Rho GTPase activation. Some studies showed that PTK7 regulates the balance between the Wnt canonical and noncanonical pathways by interacting with Dishevelled (26,46), ROR2 (42,47), b-catenin (25), and LRP6 (39). We unsuccessfully tried to identify downstream pathways that could be regulated by Ptk7 in HSCPs using a candidate gene/ protein approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of its specific binding partners and the multifunctional role of PTK7 in cell migration are yet to be elucidated. It is likely that in different cell systems, PTK7 is involved in the interactions with Plexin1 (41), receptor for activated protein kinase C (RACK1) (40), vascular endothelial growth factor receptor 1 (FLT-1) (39), disheveled (dsh) (43), Van Gogh-like 2 (VANGL2) (17,30) and ␤-catenin (48).…”
Section: Discussionmentioning
confidence: 99%
“…(15) Also, PTK7 interacts with b-catenin, enhancing b-catenin-dependent transcriptional events. (16) These studies suggest that PTK7 plays a role in the canonical Wnt pathway, the non-canonical Wnt pathway, and the PCP signaling pathway.…”
mentioning
confidence: 99%